2013
DOI: 10.4236/jep.2013.46071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals, pH, Organic Matter and Organic Carbon in Roadside Soils in Makurdi Metropolis, Benue State, Nigeria

Abstract: Roadside soil samples were collected from four sites (heavy traffic area (Wurukum); industrial site (Gboko road); residential area (Federal Lowcost) and Federal Medical Center (Wadata) representing different activities across the Benue Metropolis. At each of the sample site, roadside soils were collected at different distance from the edge of the main road (2, 10, 30, 40 and 60 meters). In each of the distance, roadside soil were collected at three depth of 0 -1 cm, 2 -4 cm and 4 -6 cm for the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
1
22
1
1
Order By: Relevance
“…Although there might be no exact point source of cadmium in the study areas (as shown by the lower concentration of cadmium compared to the other heavy metal concentrations), cadmium input might come from the pollution of cadmium from the air. Cadmium can be released into the atmosphere during heating in metal refining processes in association with copper [8]. Unlike the distribution of Pb that is related to lower pH, higher Cd concentrations might be related to the increased value of pH.…”
Section: Heavy Metal Distributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there might be no exact point source of cadmium in the study areas (as shown by the lower concentration of cadmium compared to the other heavy metal concentrations), cadmium input might come from the pollution of cadmium from the air. Cadmium can be released into the atmosphere during heating in metal refining processes in association with copper [8]. Unlike the distribution of Pb that is related to lower pH, higher Cd concentrations might be related to the increased value of pH.…”
Section: Heavy Metal Distributionsmentioning
confidence: 99%
“…Higher concentration of Pb at Pantai Watu Karung and Pantai Soge compared to the concentration at Pantai Teleng Ria and Pantai Pancer clearly showed the effect of lower pH value especially at Pantai Watu Karung (pH = 7.92). Based on the experimental study on the effect of pH on metal release and sequestration [8], it was found that found a high concentration of Pb in the low-pH experiments. This metal showed little or no release from the sediment for the high-and mid-pH experiments.…”
Section: Heavy Metal Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, alkaline reaction reduces mobility of some heavy metals and contributes to their accumulation in different soil horizons [26,27]. For this reason, the highest concentrations of heavy metals are often not found in nearsurface horizons.…”
Section: Influence Of Land Use On the Content 2583mentioning
confidence: 99%